Diagnostic Value of GATA3 and Uroplakin 3 in Differentiating Urothelial Carcinoma from Prostatic and Colorectal Carcinoma - Salama, Maha; Khairy, Dina A. (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Prostate involvement by urothelial carcinoma (UC) can occur from direct invasion. Involvement of the urinary bladder by prostate adenocarcinoma (PAC) may similarly occur, representing a common diagnostic problem especially in high-grade tumors. Furthermore, colorectal carcinoma (CRC) invades the urinary bladder which represents another challenging task for the pathologists, a problem not only in the urinary bladder but also in lymph node metastasis. Uroplakin 3 has been used for differentiation but unfortunately, its sensitivity is not so high especially in high-grade cases. Recently, GATA3 was recognized as being involved in development of urothelium. AIM: Few studies elaborated its expression in high-grade UC; therefore, this study aimed at evaluating GATA3 and comparing it to uroplakin 3 expression in differentiating the three tumors from each other. MATERIALS AND METHODS: Sixty paraffin blocks collected and distributed as 20 cases of invasive UC, 20 cases of PAC, and 20 cases of CRC, all high grade, to be studied immunohistochemically against GATA3 and uroplakin 3. RESULTS: GATA3 expression was positive in 80% of UC compared to none of the cases of PAC or CRC. The sensitivity of GATA3 in diagnosing UC was 80% whereas the specificity was 100%. Uroplakin 3 was positive in 50% of UC compared to none of the cases of PAC or CRC. The sensitivity of uroplakin 3 in diagnosing UC was 50% whereas the specificity was 100%. GATA3 and uroplakin 3 showed statistically significant inverse relation with lymphovascular and muscle invasion. CONCLUSION: GATA3 is more sensitive than uroplakin 3 for UC that can be effectively used to exclude PAC and CRC. Moreover, GATA3 and uroplakin 3 expression significantly decreases with lymphovascular invasion as well as muscle proper invasion which emphasizes their good prognostic role.